Understanding the control of yield formation in two- and six-row winter barley varieties to target disease management - Beattie, Robert John (The University of Edinburgh, 2020)
To improve the sustainability of cereal production, fungicides should only be applied to crops where they are likely to result in an economic increase in yield or grain quality. In recent times, there has been increased utilisation by growers of hybrid six-row barley varieties due to their high yields in recommended list trials in both the UK and Ireland. Six- and two-row winter barley differ in their yield components, with studies showing that sixrow types produce fewer ears m-2 and more grains ear-1 (leading to an overall higher number of grains m-2), but a lower average (mean) grain weight when compared with two-row varieties. It was hypothesised that a six-row variety would require a different approach to the management of disease compared to a two-row. Six-rows might require greater protection post-anthesis to maximise assimilate supply for grain filling whereas current barley recommendations, developed for two-rows, emphasise protection pre-flowering to maximise the development of grain sink capacity. This is because yield formation in six row varieties, with their larger number of grains may be more source-limited (limited by the supply of assimilates) than in two-row varieties where yield is generally considered to be sink-limited (limited by the number and storage capacity of grains). The main objectives of this project were to 1) compare the responses of a two-row and a six-row winter barley variety to fungicide programmes with different timings of application; 2) determine the source-sink balance of a two-row and six-row barley variety grown with and without fungicide treatment and 3) determine the relative sensitivity of grain sink capacity to variations in pre-anthesis assimilate supply during ear development in both two- and six-row varieties. To investigate if the disease management strategy needs to be modified according to row- type a field experiment to investigate the yield response to fungicide application timing in a conventional two- (cv KWS Tower) and hybrid six-row (cv Volume) winter barley variety was carried out over three years (2014/2015, 2015/2016 and 2016/2017) at two sites, SRUC, Edinburgh, Scotland and Teagasc, Oak Park Carlow, Ireland. The fungicide applications were applied as part of programmes, ranging from untreated to a four spray programme. The results showed that despite the markedly different yield components of each variety there was no significant interaction between variety and fungicide application (p>0.05) suggesting that disease management does not need to be tailored to ear type. Surprisingly there was a significant yield response to fungicide application at ear emergence, which had not been seen in barley previously. It was hypothesised that either this response resulted from a failure to effectively control ramularia at GS49 or that the response was unique to the two varieties selected for the current study. To test these hypotheses, a further field experiment was carried out at two sites in 2018. Two additional varieties were included to those used previously, a conventional two- (cv KWS Cassia) and six-row variety (cv KWS Kosmos). Fungicide treatments focused on late-season disease control. The results again indicated that there was no difference (p>0.05) in how yield of the contrasting ear types responded to fungicide treatment. When ramularia was effectively controlled at GS49, there was no requirement for a later fungicide treatment at ear emergence. To investigate the source-sink balance during grain filling of cv KWS Tower and cv Volume, a field experiment was carried out at Teagasc, Oak Park in 2016 and 2017. The relative source-sink balance was determined in two ways; firstly by growth analysis and measurement of radiation interception, radiation use efficiency and utilisation of soluble carbohydrate reserves, and secondly by manipulation treatments to alter the assimilate supply per unit grain number 14 days after flowering by row opening, de-graining, and shading. The results indicated that despite the higher grain numbers and smaller MGW in the six-row variety Volume, the source-sink balance in fungicide treated and untreated crops were similar to that of the two-row variety Tower. For both ear types, when disease was allowed to develop in untreated crops, the sink capacity (grain number and potential grain weight) was reduced as well as the source capacity, such that the crops remained sink-limited during grain filling. The results from the above experiment indicated that the lower grain weight in the six-row variety was not the result of source limitation of grain filling associated with its higher grain number, but rather a smaller potential grain weight. This raises an important question as to the control of grain sink capacity (grain number and potential grain weight). Previous research suggests that the components of sink capacity may be determined pre-anthesis. Thus, the sensitivity of sink capacity to pre-anthesis assimilate supply was tested in both Tower, and Volume in a field experiment carried out in Teagasc, Oak Park in 2017 and 2018. Pre-anthesis assimilate supply was manipulated through shading and row-opening, with investigations of the effects of these treatments on sink capacity carried out on tagged main stems. The results showed that manipulations significantly affected pre-anthesis growth conditions with shoot growth rate and carpel weight being increased (p<0.05) in both varieties when rows were opened and decreased when shaded. However, these changes in pre-anthesis growth conditions and carpel weight did not translate into effects on either MGW or grains ear-1. The results of this study raise important questions about the control of potential grain weight, as the previously held view of a direct relationship between MGW and carpel weight at anthesis is not supported. It is clear that further work into the mechanisms controlling potential grain weight in barley is required. If better understood, yield potential could be raised. The results of this research show that disease management strategies designed for two-row winter barley are also suitable for six-row varieties because the source-sink balance of the two variety types is comparable. The greatest yield response to fungicide application comes from applications made at the start of stem extension and during booting. There may be opportunities for omitting earlier applications during tiller production depending on the severity and type of the disease present in the crop.
Keywords: crop yield; fungicide application timing; sink limitation of yield; light availability; hybrid six-row winter barley; six-row winter barley; storage capacity of grain; barley